DAMPAK PRAKTIK RENTENIR TERHADAP PEREKONOMIAN MASYARAKAT GAMPONG KRUENG LALA KECAMATAN MILA KABUPATEN PIDIE - Marzuki, Fakrurradhi; Benazir, Benazir (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2023)
The purpose of this study was to determine the impact of moneylender practices on the economy of the people in the village of Krueng Lala, Mila District, Pidie Regency. The research method used is descriptive qualitative research with a phenomenological approach, while the data collection technique the author uses is observation and interviews with 10 people from the community who take loans from moneylenders. Based on the results of the study, it can be concluded that the impact of moneylender practices on the community's economy in the village of Krueng Lala, Mila District, Pidie Regency, is a negative impact on the community's economy. This can be seen from the business that some people are involved in, which does not run smoothly, even some people who work as traders close their businesses. The income received by the community is not in line with expectations before taking the loan, even the income earned has decreased from the income received daily. As well as difficulties in meeting household needs and buying goods used for trading, they even have to owe to wholesalers so they can sell as usual because their income does not meet their daily needs and buy trading needs.